ALAT BANTU JALAN UNTUK MENUMBUHKAN MINAT BERJALAN TUNADAKSA DI YAYASAN PEMBINAAN ANAK CACAT (YPAC) PANGKAL PINANG - Ariksa, Jeri; Setiawan, Yudi; Wijianti, Eka Sari; Saparin, Saparin; Darmawan, Budi (Dharma Pengabdian Perguruan Tinggi (DEPATI), 2023)
SLB YPAC Pangkal Pinang is one of the schools that provides educational services for children with special needs. This community service departs from the visit of the University of Bangka Belitung to YPAC Pangkal Pinang, In the meeting, there were several things that were of concern as an effort to create collaboration in the development of education for children with special needs. To the Collaboration of UBB and YPAC, at this time we from Mechanical Engineering will focus on children with disabilities, currently our partners from the Foundation for the Education of Disabled Children complain about the absence of tools for children with disabilities, the results of our interview with the chairman of YPAC Pangkal Pinang that children with disabilities will be better if given a tool for them to practice walking, so that they can immediately feel the sensation of walking like humans in general even though it uses aids. Currently we have succeeded in making a walker for children with disabilities and can be utilized by YPAC Pangkal Pinang. The tool can function as it should and we make the tool more flexible to be used by several children of different ages.